All plasma products are not created equal: Characterizing differences between plasma products. (June 2015) - Spinella, Philip C.; Frazier, Elfaridah; Pidcoke, Heather F.; Dietzen, Dennis J.; Pati, Shibani; Gorkun, Oleg; Aden, James K.; Norris, Philip J.; Cap, Andrew P.
Abstract : BACKGROUND: Plasma can be manufactured by multiple methods. Few studies have compared quality parameters between plasma products that may affect efficacy and safety. METHODS: Four different plasma products were analyzed to include fresh frozen plasma (FFP), liquid plasma (LP), solvent detergent plasma (SDP), and a spray-dried, solvent detergent–treated plasma (SD-SDP) at multiple time points of storage. Parameters measured included red blood cell, platelet, and white blood cell counts; microparticle phenotypes; thrombin generation; and thrombelastography. These parameters were compared in 10 samples of each product. RESULTS: SDP and SD-SDP contained the smallest number of residual cells compared with FFP and LP. Platelets were the most common residual cell in all products and were highest in LP. FFP contained the greatest number of residual red blood cells. Total microparticle counts were elevated in LP and FFP compared with SDP and SD-SDP. Cell-derived microparticles in both LP and FFP were mostly platelet in origin. Microparticle counts in SDP and SD-SDP were negligible. Thrombelastography results demonstrated similar thrombin, fibrinogen, and platelet function on Day 28 LP compared with Day 5 thawed FFP. Thrombin generation assays revealed that the total, lag time to, and peak thrombin formation were higher in SDP and SD-SDP compared with FFP and LP. All parameters in FFP and LP products were characterized by a large degree of variability. CONCLUSION: The differences in cellular, microparticle, and functional hemostatic parameters measured between plasma products have the potential to affect efficacy and safety. Further study is needed to elucidate the potential immune effects of the cellular and microparticle differences noted as well as the clinical implications of altered thrombin generation kinetics in SD products. Abstract : Supplemental digital content is available in the text.